Reflections on School Governance: The Lived Experiences of School Heads - Almagro, Agnes; Bacang, Angela Gabrielle; Calumpang , Erlinda (Journal of Interdisciplinary Perspectives, 2025)
Effective school governance is a critical foundation for achieving quality education, particularly in resource-constrained environments prevalent in many regions of the Philippines. However, the experiences of school heads in these challenging contexts remain inadequately explored. This phenomenological study investigated the lived experiences of six elementary school heads from Siaton Districts 1, 2, 3, and 4 in the Division of Negros Oriental to understand better the leadership challenges they encounter. Participants were selected through purposive and snowball sampling, ensuring a strong alignment with the research focus. Data were gathered using semi-structured interviews conducted between December 2024 and February 2025 and analyzed using Colaizzi’s seven-step method to extract significant statements, formulate meanings, and identify overarching themes. The findings revealed that school heads confronted multifaceted barriers, including limited physical resources, multi-grade instructional demands, administrative burdens, and struggles to establish authority among older teaching staff. Despite these challenges, participants demonstrated resilience through continuous professional development, strategic adaptability, mentorship engagement, and collaborative leadership practices. Their narratives underscored the importance of sustained training, supervisory support, and community partnerships in enhancing the effectiveness of governance. This study highlights the pressing need for comprehensive interventions, including structured leadership training, mentorship programs, policy reforms, and improved resource allocation, to empower school heads in marginalized communities. By addressing these gaps, educational policymakers and institutions can strengthen the leadership capacities of school heads, ensuring that they are better equipped to manage schools effectively, promote inclusive learning environments, and contribute to long-term educational improvement, particularly in underserved areas.